2021
DOI: 10.14366/usg.20143
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and ultrasound-guided fine-needle aspiration biopsy can predict a heavy nodal metastatic burden in early-stage breast cancer

Abstract: Ultrasound and ultrasound-guided fine needle aspiration biopsy can predict heavy nodal metastatic burden in early-stage breast cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…And this agreed with the results reported by Kim et al (2015), who studied 201 thyroid nodules and found that the presence of coarse calcifications did not influence the RFA outcome at 6 or 12 months (P 0.68 and 0.94 respectively); no difference was found in nodule's reduction after RFA. Our results also were in agreement with results reported by Ahn et al (2021), which included A total of 22 benign thyroid nodules from 19 patients treated with RF ablation between March 2010 and January 2013 which found that calcifications were not significantly correlated with VRR (P>0.05).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…And this agreed with the results reported by Kim et al (2015), who studied 201 thyroid nodules and found that the presence of coarse calcifications did not influence the RFA outcome at 6 or 12 months (P 0.68 and 0.94 respectively); no difference was found in nodule's reduction after RFA. Our results also were in agreement with results reported by Ahn et al (2021), which included A total of 22 benign thyroid nodules from 19 patients treated with RF ablation between March 2010 and January 2013 which found that calcifications were not significantly correlated with VRR (P>0.05).…”
Section: Discussionsupporting
confidence: 93%
“…He found that the median basal volume was 20.7 mL, and this significantly decreased after RFA at 6 months (7.3 mL (−63.5%) and at 12 months (6 mL (−70%), P vs 6 months = 0.009). Another study done by Ahn et al (2021), which included A total of 22 benign thyroid nodules from 19 patients treated with RF ablation between March 2010 and January 2013. The internal and external factors of these nodules were retrospectively reviewed and correlated with the therapeutic success and the volume reduction ratio (VRR).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sensitivity and specificity of ABUS in predicting heavy nodal metastases were statistically similar to those of HHUS and those previously reported [ 17 24 ]. Among the diagnostic performance metrics, the NPV of ABUS was the highest, similar to that of HHUS and comparable to that previously reported (93%) by Luo et al [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…Reviewers first evaluated the presence of identifiable benign-looking or suspicious axillary LNs on ABUS images and then evaluated the LNs based on the following findings: hilum compression or loss, uneven or even cortical thickening > 3-mm, focal hyperechoic cortical change, LN shape (oval, round, or irregular), circumscribed or non-circumscribed LN margins, and presence of extranodal extension [ 16 ]. Any of the following US findings were considered abnormal: hilum compression or loss, > 3-mm uneven cortical thickening, > 3-mm cortical thickening, focal hyperechoic cortical change, round or irregular shape, non-circumscribed margin, and extranodal extension of axillary LNs [ 16 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…AUS is recommended during the clinical work-up and staging of newly diagnosed breast cancer to predict the axillary metastatic tumor burden which in turn guides clinical management of the axilla and helps to triage patients for preoperative systemic therapy [16] , [17] , [18] , [19] . Our observation of cortical thickness ≥ 5.4 mm as well as displacement or loss of the hilum are AUS features predictive of malignancy, consistent with the findings of other investigators [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%